Social Work at the Intersection of Disability and Displacement: Rethinking Our Role. Issue 1 (2nd January 2020) - El-Lahib, Yahya
ABSTRACT: This article reports on a Critical Discourse Analysis study that focused on examining the intersection of disability, displacement, and social work. Situated within a critical understanding of the social justice role of social work, the study examined how dominant discourses of "opportunity" perpetuate oppression of people with disabilities and shape service provision. Findings discussed in this article emerged from narrative episodic interviews with 23 participants who shared stories about their experiences as immigrants and refugees with disabilities, as family members of immigrants or refugees with disabilities, or as service providers in settlement practice settings. These findings demonstrate that dominant discourses of opportunity reflect, reinforce and perpetuate ableism, racism, and colonialism, and suggest that social work as a profession is implicated in facilitating the operation of such discourses through efforts to actualize opportunity. Implications of these findings for social work practice are identified and discussed.